(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: This study aimed to investigate the levels of anxiety, depression, and health-related quality of life (HRQoL) among health science students at selected universities in Ho Chi Minh City (HCMC) and identify related factors. Methods: A cross-sectional descriptive study was conducted with 398 health science students from four universities in HCMC in 2024. Anxiety and depression were measured using the Depression Anxiety Stress Scales (DASS-21); HRQoL was assessed by EQ-5D-5L. Data analysis employed Chi-square and ANOVA tests with a significance level set at p ≤ 0.05. Results: More than 65% of students exhibited symptoms of anxiety and depression ranging from mild to severe levels, with 28.39% classified as extremely severe. The average EQ-5D-5L score was 0.851 ± 0.107, lower than the general population average. Factors significantly associated with DASS-21 scores included gender, academic year, marital status, financial situation, difficulties making new friends, exam failures, and a history of anxiety/depression. Students in their second and fifth academic years, living away from family, or experiencing financial difficulties reported significantly lower HRQoL. There was a significant negative correlation between DASS-21 scores and EQ-5D-5L scores (r = -0.142; p = 0.004). Conclusion: Anxiety and depression among health science students in HCMC were relatively high, negatively affecting their QoL. The study recommends universities, and relevant institutions implement psychological support programs, reduce academic and economic pressures, thereby enhancing mental health and quality of life for students.